The Study of Search Engine Optimization on Website as a Marketing Strategy on the Internet - Dwi Mandasari Rahayu; Agung Budi Prasetyo (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2020)
The Internet usages have been growing. The marketing ways for both products and services have changed into the internet media. Cross-country target market and 24-hour services become the main strengths of online marketing. Moreover, the cost of promotion on the internet marketing is more effective than conventional media such as television, radio, and newspapers. It needs some right strategies and methods to get many visitors. The websites used as marketing media must be built with the right rules to become the optimum internet marketing. One of the rules to build internet marketing is optimizing website to be indexed properly in search engines like Google. This research method is on-page and off-page observation of web pages. Consequently, the analyzed web pages have met the marketing rules based on SEO. However, many other aspects still need improvement.